A Comprehensive Review On The Influence Of Equal Channel Angular Pressing Parameters On Magnesium Alloys - Salleh, Mohd Shukor; Ab Rahman, Azhan; Yahaya, Saifudin Hafiz; Yaakob, Mohd Yuhazri; Akmal, Suriati (International Research Publication House, 2020)
Equal channel angular pressing (ECAP) is a promising technique to produce an ultra-fine grain microstructure thus improving the properties of the material. Several factors have been acknowledged to have an affect on the microstructure and mechanical properties of the material after an ECAP process which include the operation temperature, number of passes, die angle and also the processing route. Therefore, this review paper gives a concise summary on the influence of ECAP parameters towards the microstructure and mechanical properties of magnesium alloys. Specific attention has been given to the magnesium alloy microstructure evolution and its mechanical properties after ECAP process. It was discovered that refined microstructure with better mechanical properties can be produced at lower temperature, higher number of passes and smaller die angle. It was also noticed that using route BC of ECAP process may give the best results by contributing about 28% of material hardness compared to the other routes.